IMproving facial PRosthesis construction with contactlESs Scanning and Digital workflow (IMPRESSeD): study protocol for a feasibility crossover randomised controlled trial of digital versus conventional manufacture of facial prostheses in patients with orbital or nasal facial defects - Rachael Y. Jablonski; Trevor J. Coward; Paul Bartlett; Andrew J. Keeling; Chris Bojke; Sue H. Pavitt; Brian R. Nattress (Pilot and Feasibility Studies, 2023)
Abstract Background Facial prostheses can have a profound impact on patients’ appearance, function and quality of life. There has been increasing interest in the digital manufacturing of facial prostheses which may offer many benefits to patients and healthcare services compared with conventional manufacturing processes. Most facial prosthesis research has adopted observational study designs with very few randomised controlled trials (RCTs) documented. There is a clear need for a well-designed RCT to compare the clinical and cost-effectiveness of digitally manufactured facial prostheses versus conventionally manufactured facial prostheses. This study protocol describes the planned conduct of a feasibility RCT which aims to address this knowledge gap and determine whether it is feasible to conduct a future definitive RCT. Methods The IMPRESSeD study is a multi-centre, 2-arm, crossover, feasibility RCT with early health technology assessment and qualitative research. Up to 30 participants with acquired orbital or nasal defects will be recruited from the Maxillofacial Prosthetic Departments of participating NHS hospitals. All trial participants will receive 2 new facial prostheses manufactured using digital and conventional manufacturing methods. The order of receiving the facial prostheses will be allocated centrally using minimisation. The 2 prostheses will be made in tandem and marked with a colour label to mask the manufacturing method to the participants. Participants will be reviewed 4 weeks following the delivery of the first prosthesis and 4 weeks following the delivery of the second prosthesis. Primary feasibility outcomes include eligibility, recruitment, conversion, and attrition rates. Data will also be collected on patient preference, quality of life and resource use from the healthcare perspective. A qualitative sub-study will evaluate patients’ perception, lived experience and preference of the different manufacturing methods. Discussion There is uncertainty regarding the best method of manufacturing facial prostheses in terms of clinical effectiveness, cost-effectiveness and patient acceptability. There is a need for a well-designed RCT to compare digital and conventional manufacturing of facial prostheses to better inform clinical practice. The feasibility study will evaluate key parameters needed to design a definitive trial and will incorporate early health technology assessment and a qualitative sub-study to identify the potential benefits of further research. Trial registration ISRCTN ISRCTN10516986). Prospectively registered on 08 June 2021,  https://www.isrctn.com/ISRCTN10516986 .